Progress in renewable electricity in Northern Europe towards EU 2020 targets. (December 2015) - Cross, Sam; Hast, Aira; Kuhi-Thalfeldt, Reeli; Syri, Sanna; Streimikiene, Dalia; Denina, Arta
Abstract: Within the EU׳s attempt to establish "world leadership" on energy and climate policy, Renewable Energy is an important component, with legally binding Renewables targets for 2020 established under the 2009 Renewables directive. The directive obliges EU Member states to provide "National Renewable Energy Action Plans", setting out a detailed pathway to reaching their national-level Renewables targets under the directive. We compare actual progress in renewable electricity development against the intentions in the plans for the years 2011 and 2012, and we assess whether there are significant risks visible on failing to reach the targets. Five countries in the Nordic-Baltic region are studied: Sweden, Finland, Latvia, Lithuania and Estonia. These states have historical success in bioenergy and hydro development, but in general have limited experience in wind power and minimal use in solar power. We find that all five states are reaching their overall RES Electricity objective, but some countries are underperforming in newer RES technologies (e.g. wind), compensating for this by over-performing in more established technologies (e.g. biomass). This raises concern, since utilization of all available technologies will be needed to reach the 2020 targets.